Strategies and technical training and perception of psychological help youth football - Olmedilla Zafra, A.; Ortega Toro, E.; Boladeras Esteve, A.; Ortín Montero F. J.; Bazaco Belmonte, M. J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
The objective of this study is to present three psychological training programs implemented in youth football teams and determine if there are differences in the value and satisfaction that players make themselves regarding crafted programs. The sample consisted of 83 players belonging to 6 youth teams participating in the National Youth League Football Federation of the Region of Murcia, aged between 16 and 19 years (M = 17.54, SD = 0 , 82). To assess satisfaction with psychological training program developed a questionnaire consisting of 10 items on a Likert scale with three response groups (I helped [1 = somewhat, 5 = long] I hindered [- 1 = bit; -5 = much], and not affected me = 0), also included two open questions. The psychological training program was conducted along a season. The results indicate no significant differences between the valuations of the players make their psychological training programs. All three groups received appreciation for the program, noting that the greatest satisfaction came in the same G2. The highest rated program included learning psychological techniques such as arousal control, relaxation and visualization, plus the players suggest increasing the number of psychological training sessions.